Efficacy of Heparinoid PSS in Treating Cardiovascular Diseases and Beyond—A Review of 27 Years Clinical Experiences in China. (April 2016) - Zeng, Yangyang; Yang, Desheng; Qiu, Peiju; Han, Zhangrun; Zeng, Pengjiao; He, Yanli; Guo, Zhihua; Xu, Lingling; Cui, Yidi; Zhou, Zijing; Zhang, Meng; Hao, Jiejie; et al.
Propylene glycol alginate sodium sulfate (PSS) is the world's first oral heparinoid approved by Chinese Food and Drug Administration in 1987. Propylene glycol alginate sodium sulfate is produced by modifying partially hydrolyzed alginate, one of the most abundant marine polysaccharides isolated from brown algae, by epoxypropane esterification and by chemical sulfation. It is used for treating and preventing cardiovascular-related diseases. The low cost (US$1.29/100 tablets, ∼4 tablets/day), remarkable clinical effects, and convenient oral administration make PSS an ideal long-term prevention drug. Propylene glycol alginate sodium sulfate is available in most drug stores in China, and millions of patients take PSS routinely during the past 27 years. The 22 784 reported clinical cases as well as the structure, preparation, clinical efficacy, adverse reactions, pharmacokinetics, pharmacodynamics, and future perspectives of PSS based on the results of peer-reviewed publications will be discussed. This review should bring the knowledge of PSS gained in China to the world to stimulate in depth academic and clinical studies of PSS.